Anticyclonic eddies increase accumulation of microplastic in the North Atlantic subtropical gyre. (January 2018) - Brach, Laurent; Deixonne, Patrick; Bernard, Marie-France; Durand, Edmée; Desjean, Marie-Christine; Perez, Emile; van Sebille, Erik; ter Halle, Alexandra
Abstract: There are fundamental gaps in our understanding of the fates of microplastics in the ocean, which must be overcome if the severity of this pollution is to be fully assessed. The predominant pattern is high accumulation of microplastic in subtropical gyres. Using in situ measurements from the 7th Continent expedition in the North Atlantic subtropical gyre, data from satellite observations and models, we show how microplastic concentrations were up to 9.4 times higher in an anticyclonic eddy explored, compared to the cyclonic eddy. Although our sample size is small, this is the first suggestive evidence that mesoscale eddies might trap, concentrate and potentially transport microplastics. As eddies are known to congregate nutrients and organisms, this phenomenon should be considered with regards to the potential impact of plastic pollution on the ecosystem in the open ocean. Graphical abstract: Highlights: Discussion of the heterogeneity of surface plastic debris distribution at sea In situ measurements and correlation with satellite observations Rationalization by the local circulation in eddies